(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
Peripheral nerve injuries, like all injuries nowadays, have several negative complications and consequences in the affected patient’s life. As a result of the statistical studies of many authors, the frequency of peripheral nerve damage is 4-11%. Among these injuries, a large number of them are injuries of the median nerve (N Medianus), which is considered one of the reasons for the impairment of the functional state of the working part and the inability to work for a long time, leading to the disruption of human labor activity. kaitarish is considered one of the most relevant aspects of modern medicine